Comparison and outcome analysis of patients with apical and non-apical takotsubo cardiomyopathy - El-Battrawy, Ibrahim; Behnes, Michael; Ansari, Uzair; Hillenbrand, Dennis; Haghi, Dariusch; Hoffmann, Ursula; Papavassiliu, Theano; Elmas, Elif; Fastner, Christian; Becher, Tobias; Baumann, Stefan; Dösch, Christina; et al. (QJM, 2016)
Background: Takotsubo cardiomyopathy (TTC) is a relevant differential diagnosis in patients presenting with signs of an acute coronary syndrome. Although recent